UNIVERSITY IMAGE: NEW APPROACH AND PERSPECTIVE THEORETICAL AND PRACTICAL DECISIONS - Melnikas, Borisas (Ekonomika, 2011)
Greta Drūteikenė, Albinas Marčinskas. Universiteto įvaizdžio kaita. Vilnius: Vilnius University, 2010. 320 p.